Two new cavernicolous species of Pseudochthonius Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from Lagoa Santa karst, Minas Gerais, Brazil - Schimonsky, Diego Monteiro Von (Zootaxa, 2024)
Two new pseudoscorpion species of the genus Pseudochthonius Balzan, 1892 are described from caves in the Lagoa Santa karst area in Southeast Brazil. Pseudochthonius limettioides sp. nov. was collected in ten caves and is a troglobite that lacks eyes and body pigmentation. Pseudochthonius lundi sp. nov. was collected in three caves and is considered a troglophile with only one pair of eyes. Both species might be threatened by mining projects and more studies are needed to better understand many aspects of their biology.